2017
DOI: 10.1590/1678-457x.06117
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of soybean oil added to coffee husk extract (Coffea arabica L.) under accelerated storage conditions

Abstract: Several plants have been studied as potential sources of natural antioxidants for use in the food industry, especially polyphenols. The aim of this study was to evaluate the effects of hydroalcoholic extract from coffee husk on the oxidative stability of soybean oil when stored in an oven. Samples were maintained at a temperature of 60 °C and their oxidative stability was evaluated once every 5 days for a period of 20 days through the Rancimat equipament and analysis of peroxide value, conjugated dienes and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
3
7
0
1
Order By: Relevance
“…Before frying, the induction times determined with the Rancimat corresponded to 4.32 h (SI) and 11.02 h (SO), and those with the RapidOxy were 27.6 min (SI) and 40.2 min (SO). The Rancimat SI value was similar to that (4.07 h) reported by Varas Condori et al (2020) for linseed oil under the same analysis conditions, while the SO result was within those (6.00 h and 16.79 h) reported by Ribeiro and Jorge (2017) and Farhoosh (2007), respectively. Higher times (17.6 h) were described for sacha inchi oil by Gutiérrez et al (2019) for a Rancimat test performed at 80 °C.…”
Section: Oxidation Stabilitysupporting
confidence: 87%
“…Before frying, the induction times determined with the Rancimat corresponded to 4.32 h (SI) and 11.02 h (SO), and those with the RapidOxy were 27.6 min (SI) and 40.2 min (SO). The Rancimat SI value was similar to that (4.07 h) reported by Varas Condori et al (2020) for linseed oil under the same analysis conditions, while the SO result was within those (6.00 h and 16.79 h) reported by Ribeiro and Jorge (2017) and Farhoosh (2007), respectively. Higher times (17.6 h) were described for sacha inchi oil by Gutiérrez et al (2019) for a Rancimat test performed at 80 °C.…”
Section: Oxidation Stabilitysupporting
confidence: 87%
“…Agro-food products, by-products, and wastes contain several bioactive compounds that can be used for developing functional products (Tinello, Mihaylova, & Lante, 2018). In this regard, soybean oil has been previously enriched with plant extracts derived from olive leaf (Taghvaei et al, 2014), aromatic plants (Saoudi et al, 2016), rosemary (Yang et al, 2016), grape seed (Freitas et al, 2017), coffee husk (Ribeiro & Jorge, 2017), peanut skin (Franco et al, 2018), and goji berry (Pedro et al, 2018) to improve oxidative stability.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been previously carried out with plant extracts to prevent oxidative deterioration. Among them, olive leaves [ 118 ], some aromatic plants [ 119 ], rosemary, rambutan, fruit peel [ 120 ], grape seed [ 121 ], cocoa bean shell [ 122 ], coffee husk [ 123 ], peanut skin [ 124 ], Cressa cretica L. leaves [ 125 ], goji berry [ 126 ], marjoram, thyme, ginger, turmeric [ 127 ], oregano [ 15 ], watermelon [ 96 ]. It has been shown that soybean oil enriched with olive leaf extract showed lower peroxide value and a lower amount of secondary product compared to the control [ 118 ].…”
Section: Enrichment Of Oils With Natural Antioxidantsmentioning
confidence: 99%